A Study to Assess the Quality of Life among Caregivers of Patients of Schizophrenia in a Tertiary Care Centre of Western Maharashtra - Sheroun, Deepika; Das, Radhika (International Journal of Nursing Research, 2023)
Introduction: Treatment of the chronic mentally ill like patients of schizophrenia, mainly focuses on the patient and the caregivers get no attention. In bargain to providing care to patients, these caregivers experience poor quality of life (QOL). Aims and Methods: The present paper reports on the QOL of caregivers of schizophrenia patients attending the OPD of a tertiary care center in, Maharashtra India. Thirty caregivers were selected, with age between 20 and 50 years and providing care for more than 1 year after taking consent from them. Data were collected using WHOQOL BrefScale. Results: The four domains – physical health, social relationship, psychological, and environmental factors, were used to understand the QOL of the caregivers. The domain with the highest score was environmental factors (mean is 59.7), which consists of the following factors: Financial resources freedom, physical safety, and security health and social care, opportunities for acquiring new information, etc. The domain with the least score was physical health (54.65), related with the following factors – activities of daily living, fatigue mobility pain, discomfort sleep, and rest work capacity. Psychological and social relationship scores were 58.2 and 59.0, respectively. Conclusion: In this study, the QOL of these caregivers was obtained lowest in the physical domain. It is evident that the caregivers suffer from fatigue, insomnia, and their activities of daily living are hampered in the behest of caring for their loved one.